Accuracy comparison of implant impression techniques: A systematic review - Moreira, António Herculano Jesus (2015)
Background Several studies link the seamless fit of implant-supported prosthesis with the accuracy of the dental impression technique obtained during acquisition. In addition, factors such as implant angulation and coping shape contribute to implant misfit. Purpose To identify the most accurate impression technique and factors affecting the impression accuracy. Material and Methods A systematic review of peer-reviewed literature was conducted analyzing articles published between 2009 and 2013. The following search terms were used: implant impression, impression accuracy, and implant misfit. A total of 417 articles was identified, 32 were selected for review. Results All 32 selected studies refer to in vitro studies. Fourteen articles compare open and closed impression technique, 8 advocate the open technique and 6 report similar results. Other 14 articles evaluate splinted and non-splinted techniques; all advocating the splinted technique. Polyether material usage was reported in 9; 6 studies tested vinyl polysiloane and 1 study used irreversible hydrocolloid. Eight studies evaluated different copings designs. Intra-oral optical devices were compared in 4 studies. Conclusions The most accurate results were achieved with two configurations: (1) the optical intra-oral system with powder; and (2) the open technique with splinted squared transfer copings, using polyether as impression material.